Pemberdayaan Masyarakat dalam Perspektif Kepemimpinan Kepala Kampung Bulusari Berdasarkan Undang-Undang Desa - Pratama, Rendi; Sainul, Sainul (Kolaborasi Masyarakat, 2026)
Low community participation resulting from centralistic leadership patterns remains a primary obstacle in village development, suggesting that the effective implementation of Law Number 6 of 2014 requires strengthening through inclusive leadership models. This study aims to conduct an in-depth analysis of the relationship between the leadership pattern of the Village Head of Bulusari and the effectiveness of community empowerment programs in Central Lampung Regency. A descriptive qualitative approach was employed, with data gathered through in-depth interviews with key informants (the Village Head, hamlet heads, and residents), non-participant observation, and documentary studies, followed by a reductive-categorical analysis. The findings reveal that empowerment in Bulusari Village is manifested through both physical schemes (irrigation infrastructure and roads) and non-physical initiatives (nutritional health and youth development). The Village Head implements a progressive-participatory leadership style that integrates instructive, consultative, and participatory functions throughout every stage of policy-making. Nevertheless, community participation has not yet reached an optimal level due to structural barriers, specifically low collective awareness and village budget constraints. This research contributes to the development of village leadership models based on strengthening social capital as a prerequisite for village autonomy, in alignment with national regulatory mandates.